2012
DOI: 10.1074/jbc.m111.329987
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation Receptor CLEC-2 Regulates Blood/Lymphatic Vessel Separation by Inhibiting Proliferation, Migration, and Tube Formation of Lymphatic Endothelial Cells

Abstract: Background: Mice deficient in the platelet receptor CLEC-2 for podoplanin showed impaired blood/lymphatic vessel separation. Results: Functions of lymphatic endothelial cells are inhibited by platelet releasates and BMP-9, which we identified as a novel releasate. Conclusion: Granule contents including BMP-9 released upon platelet activation by CLEC-2-podoplanin interaction may contribute to the separation in vivo. Significance: We proposed a novel mechanism of platelet-mediated blood/lymphatic vessel separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 51 publications
6
157
3
Order By: Relevance
“…Some groups have reported that platelet activation by CLEC2 signaling may regulate LEC growth in vitro through secretion of platelet granule contents (6,10). However, we have not observed such effects on LEC growth in vitro or detected major defects in the pattern or rate of lymphatic vascular development in vivo (8,11), and how such an angiogenic mechanism would explain an ongoing requirement in mature, presumably nonangiogenic, animals is not clear.…”
Section: Introductioncontrasting
confidence: 64%
“…Some groups have reported that platelet activation by CLEC2 signaling may regulate LEC growth in vitro through secretion of platelet granule contents (6,10). However, we have not observed such effects on LEC growth in vitro or detected major defects in the pattern or rate of lymphatic vascular development in vivo (8,11), and how such an angiogenic mechanism would explain an ongoing requirement in mature, presumably nonangiogenic, animals is not clear.…”
Section: Introductioncontrasting
confidence: 64%
“…Interestingly, it has been shown that during embryogenesis, lymphatic system separation from blood vessels requires platelet activity 7. Indeed, platelets regulate the blood/lymphatic vessel separation by inhibiting the proliferation, migration, and tube formation of LECs, upon the interaction of C‐type lectin‐like receptor 2 (CLEC‐2) with podoplanin 8. Platelet activity has also been shown to be required throughout life in order to maintain the lymphovenous junction integrity 5.…”
Section: Introductionmentioning
confidence: 99%
“…26 More recently, Osada et al proposed that during embryonic development, podoplanin in LECs activates platelets by binding to CLEC-2 in the connection between lymph sacs and CV and that inhibits migration, proliferation, and tube formation, which facilitates blood/lymphatic vessel separation. 27 In any case, our description that podoplanin expression only starts after LECs leave the CV is probably an indication of the LEC maturation process. Our findings emphasize the idea that the process of LEC differentiation is a stepwise process that starts in the veins but continues after the LEC progenitors leave the CV.…”
Section: Discussionmentioning
confidence: 77%